A hybrid FL-enabled ensemble approach for lung disease diagnosis leveraging fusion of SWIN transformer and CNN - Chowdhury, Asif Hasan; Islam, Md. Fahim; Riad, M Ragib Anjum; Hashem, Faiyaz Bin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.